ANALISIS USAHATANI PADI SAWAH DI DESA JAYAPURA KECAMATAN BUNGARAYA KABUPATEN SIAK PROVINSI RIAU - Ria Diana Dewi Indriyanti; Khairizal; Saipul Bahri (UIR Press, 2025)
This study aims to analyze production costs, output, revenue, income, and the efficiency of rice farming in Jayapura Village, Bungaraya District, Siak Regency, Riau Province. The study was conducted over six months, from December 2023 to May 2024, using a survey method. The study population consisted of 137 rice farmers, and a sample of 30 was selected using simple random sampling. The data used included primary and secondary data, which were then analyzed descriptively to calculate production costs, income, and business efficiency levels using the Return Cost Ratio (RCR) approach. The research results show that the average total production cost per plot per planting season is IDR 12,302,408, consisting of fixed costs of IDR 136,961 and variable costs of IDR 12,165,447, with the most significant components being fertilizers (41.54%) and labor costs (34.84%). The average production reaches 2,400 kg per plot per planting season with a selling price of IDR 8,500/kg, resulting in gross income of IDR 20,400,000 and net income of IDR 8,097,592 per plot per planting season. The RCR value of 1.66 indicates that every IDR 1.00 of cost incurred generates IDR 1.66 in income, suggesting that rice farming in the study area is efficient and feasible for sustainable development..